PEMBUATAN DAN UJI AKTIVITAS SEDIAAN GEL SCARLESS WOUND DENGAN EKSTRAK BINAHONG DAN ZAT AKTIF PIROXICAM - Ayaga Divadi; Sri Hartati Yuliani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2015)
Wound is a condition where the tissue integrity is damaged so that body will attempt to repair the damaged tissue by wound healing mechanism. This mechanism usually results in the scar formed by its inflammatory phase. Binahong (Anredera cordifolia (Ten.) Steenis) contains ascorbic acid and flavonoids which are important for collagen formation, to improve the rate of the wound healing process. Piroxicam can shorten or detain the inflammatory phase by inhibiting the cyclooxygenase (COX) enzymes in the prostaglandine synthesis process, which play an important role in scar formation. The aim of this research is to discover if the combination of piroxicam and binahong extract in the scarless wound gel could offer scar reduction effect. In this research, a gel preparation with binahong extract was combined with piroxicam to develop the scarless wound gel (BinPirox). The research was purely experimental. It was done by conducting a histopathological test followed by collagen area calculation. The data were analyzed by independent sample t-test with 95% significancy level. In this research, the addition of piroxicam was expected to reduce the scar formation on incisional wound of white Swiss Webster mice (Mus musculus). The result showed that BinPirox formed statistically less scar when compared to Bin (a gel preparation with binahong extract).